Alteration and Mineralization in the Coppo Village, Barru District, South Sulawesi Province - Muhamad Hardin Wakila; Nurliah Jafar; Agung Fiqriansyah (CV Insight Publisher, 2023)
Hydrothermal alteration can be used to interpret and identify undiscovered mineralization, and can lead to the discovery of such mineralization. In the research area, it was found that there were outcrops that were altered with the physical characteristics of weathered outcrops. The research location is in the Camba Formation of Volcano Rock Members, and there are indications of sulfide mineralization, megascopically this study took 3 (three) alteration samples, selected based on the differences in color and texture of the rocks found. Samples we reanalyzed to determine alteration mineral assemblages using petrographic and XRD analysis methods, then to determine the type of alteration in sulfide deposits in the study area using the classification by Corbett and Leach, 1996. The results of the petrographic analysis showed that sample 1 consisted of chlorite, epidote, quartz and mineral assemblages. opaque minerals, sample 2 consists of plagioclase minerals, kfeldspar, clay minerals and quartz, sample 3 consists of epidote minerals, calcite and opaque minerals. The results of the XRD analysis showed that sample 1 consisted of the minerals quartz, chlorite, epidote and pyrite, sample 2 consisted of the minerals kaolinite, illite and pyrite, sample 3 consisted of the minerals quartz, chlorite, dolomite, epidote and auricuprite. The results of the analysis of alteration minerals assemblages were classified using Corbett and Leach, 1996 and it was found that the types of alteration in the research area were propylitic and argillic alteration types.